Pregnenolone and pregnenolone-methyl-ether rescue neuronal defects caused by dysfunctional CLIP170 in a neuronal model of CDKL5 Deficiency Disorder. (1st March 2020) - Barbiero, I.; Peroni, D.; Siniscalchi, P.; Rusconi, L.; Tramarin, M.; De Rosa, R.; Motta, P.; Bianchi, M.; Kilstrup-Nielsen, C.
Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) gene are responsible for the onset of CDKL5 Deficiency Disorder (CDD), a neurological pathology characterised by severe infantile seizures, intellectual disability, impairment of gross motor skills, sleep and gastrointestinal disturbances. CDKL5 is a serine/threonine kinase the molecular network of which is not yet fully understood. Loss of CDKL5 both in vitro and in vivo leads to altered neuronal morphology including axon specification and outgrowth, dendritic arborisation and spine morphology suggesting a link between CDKL5 and the regulation of proper cytoskeleton functioning. Recently, we found that CDKL5 regulates the binding of CLIP170 to microtubules (MT). CLIP170 is a MT-plus end tracking protein (+TIP) that associates with MTs when present in its open, active conformation. Here we present evidence suggesting CLIP170 contributes to neuronal CDKL5-dependent defects and that it represents an important novel druggable target for CDD; indeed, CLIP170 is directly targeted by the neuroactive steroid pregnenolone (PREG), which induces the active conformation of the protein thus promoting MT-dynamics. We here show that PREG and a synthetic derivative pregnenolone-methyl-ether (PME) can restore the MT association of CLIP170 and revert morphological and molecular defects in Cdkl5- KO neurons at different stages of maturation. All together, these findings identify CLIP170 as possible novel druggable target for CDKL5 related disorders providing an intriguing prospective for future disease-modifying drug-based therapies. Highlights: CLIP170 has reduced affinity for microtubule plus-ends in Cdkl5-deficient cells. Pregnenolone and pregnenolone-methyl-ether can restore CLIP170 microtubule binding. Pregnenolone and pregnenolone-methyl-ether can restore CDKL5-dependent neuronal defects.